Healthy adult vaccination: An urgent need to prevent hepatitis B in China. Issue 3 (3rd March 2016) - Qiu, Yan; Ren, Jingjing; Yao, Jun
Abstract: Prevalence of hepatitis B is still high among adults in China, athough the prevalence in children has decreased dramatically. Immunization against hepatitis B among adults is urgently required. Through analyzing the immunogenicity of different doses, schedules and booster immunization among adults, we recommend 10 or 20 μg with a 0-1-6-month schedule or a 0-1-12-month schedule for migrant adults. For immunity failure, increasing the dose or covalent vaccine is suggested to provide protective antibodies. To enhance immunity among adults, hepatitis B vaccine should be included in health insurance.